A Weight Training Program And Its Effect On Increasing The Muscular Ability Of Futsal Players - Mohammad Ashor Abbas Alumairi (Musamus Journal of Physical Education and Sport (MJPES), 2026)
Background. The development of muscular ability represents a fundamental component in improving the physical performance of futsal players, as the nature of the game requires high levels of explosive strength and rapid force production within limited spaces and short time intervals. Purpose. This study aimed to identify the effect of a weight training program on increasing the muscular ability of futsal players. Materials and Methods. The study employed an experimental approach using a one-group design with pre- and post-tests. The research sample consisted of 10 futsal players from the University of Wasit team, while two players participated in the exploratory study. A weight training program was implemented for eight weeks with three training sessions per week. The research variables included absolute muscular ability of the legs, vertical jump from standing, and standing long jump. Data were analyzed using arithmetic mean, standard deviation, t-test, and percentage change. Results. The results showed statistically significant improvements between the pre- and post-measurements in all research variables in favor of the post-tests. The percentage of improvement reached 59% in absolute muscular ability of the legs, 53% in the vertical jump test, and 61% in the standing long jump test, indicating the effectiveness of the training program in developing muscular ability. Conclusions. The weight training program demonstrated a significant positive effect on enhancing the muscular ability of futsal players. The study recommends incorporating structured weight training programs within the physical preparation of futsal players, while carefully controlling training loads and intensity to maximize performance development.